2017
DOI: 10.1002/aenm.201701648
|View full text |Cite
|
Sign up to set email alerts
|

Short‐Range Order in Mesoporous Carbon Boosts Potassium‐Ion Battery Performance

Abstract: storage, sodium-ion batteries (NIBs) are attracting more attention because of the abundant sodium resource. [7][8][9] In comparison to the natural abundance of lithium (20 ppm) in the Earth's crust, the abundances of Na (23 000 ppm) and K (17 000 ppm) seem infinite. [10][11][12] Unlike NIBs, really few researches are focused on potassium-ion batteries (KIBs) in a long-trem period. Till last two years, the new concept of KIBs has begun to gain much more attention. [13][14][15][16][17] The advantages of KIBs are… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
306
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 497 publications
(323 citation statements)
references
References 42 publications
8
306
0
Order By: Relevance
“…[14,15] However,c arbonaceous materials exhibit ar elatively low reversible capacity because potassium-ion storage is limited by the insertion mechanism. [14,15] However,c arbonaceous materials exhibit ar elatively low reversible capacity because potassium-ion storage is limited by the insertion mechanism.…”
Section: Introductionmentioning
confidence: 99%
“…[14,15] However,c arbonaceous materials exhibit ar elatively low reversible capacity because potassium-ion storage is limited by the insertion mechanism. [14,15] However,c arbonaceous materials exhibit ar elatively low reversible capacity because potassium-ion storage is limited by the insertion mechanism.…”
Section: Introductionmentioning
confidence: 99%
“…Almost no capacity fading occurred after the initial 100 cycles . NonSiMPMs have similar applications as electrodes in Na‐ion batteries, Zn‐Air batteries, K‐ion batteries, and Al‐ion batteries …”
Section: Applications Of Nonsimpmsmentioning
confidence: 98%
“…Also, the Daumas–Hérold model, should also be taken into consideration while explaining the substantial increase of interlayer spacing in K‐based GICs (+60% for KC 6 ), as compared to the Li‐GICs (+11% for LiC 6 ); the related strain in the individual graphite layers should also be considered . Previous studies have demonstrated that the short‐order range was recognized to be significant for the electrochemical performances, and the decreased lateral dimensions were beneficial for higher rate performance …”
Section: Anode Materialsmentioning
confidence: 99%